Reference sources for small and medium-sized libraries - O'Gorman, Jack (ALA Editions, an imprint of the American Library Association, 2014)
Focusing on new reference sources published since 2008 and reference titles that have retained their relevance, this new edition brings O Gorman's complete and authoritative guide to the best reference sources for small and medium-sized academic and public libraries fully up to date. About 40 percent of the content is new to this edition. Containing sources selected and annotated by a team of public and academic librarians, the works included have been chosen for value and expertise in specific subject areas. Equally useful for both library patrons and staff, this resource Covers more than a dozen key subject areas, including General Reference; Philosophy, Religion, and Ethics; Psychology and Psychiatry; Social Sciences and Sociology; Business and Careers; Political Science and Law; Education; Words and Languages; Science and Technology; History; and Performing Arts Encompasses database products, CD-ROMs, websites, and other electronic resources in addition to print materials Includes thorough annotations for each source, with information on author/editor, publisher, cost, format, Dewey and LC classification numbers, and more Library patrons will find this an invaluable resource for current everyday topics. Librarians will appreciate it as both a reference and collection development tool, knowing it's backed by ALA's long tradition of excellence in reference selection.